2012
DOI: 10.14214/sf.46
|View full text |Cite
|
Sign up to set email alerts
|

From the Arctic Circle to the Canadian prairies – a case study of silver birch acclimation capacity

Abstract: . 2012. From the Arctic Circle to the Canadian prairies -a case study of silver birch acclimation capacity. Silva Fennica 46(3): 355-364.Earlier provenance research has indicated poor success even in short distance transfers (> 2-3° latitude) of silver birch (Betula pendula Roth) southward from their origin. These results may indicate poor adaptability of silver birch to a warming climate. Some of the scenarios for a warming climate in Finland suggest effective heat sums are likely to double in the north and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…Because of the inherent genetic variability and phenotypic plasticity, birch is able to adapt by natural selection to a wide range of sites and changing environmental conditions (e.g., [36][37][38]). For example, there are reports on genotype-dependent leaf area variations and root architecture adjustments in response to experimental warming or drought (e.g., [33][34][35]) and studies describing a proper acclimation of provenances when tested in warmer and drier regions [39].…”
Section: High Genetic Variability and Phenotypical Plasticitymentioning
confidence: 99%
“…Because of the inherent genetic variability and phenotypic plasticity, birch is able to adapt by natural selection to a wide range of sites and changing environmental conditions (e.g., [36][37][38]). For example, there are reports on genotype-dependent leaf area variations and root architecture adjustments in response to experimental warming or drought (e.g., [33][34][35]) and studies describing a proper acclimation of provenances when tested in warmer and drier regions [39].…”
Section: High Genetic Variability and Phenotypical Plasticitymentioning
confidence: 99%
“…Notwithstanding, the results from commercial forestry and common garden experiments indicate large acclimation capacity (i.e., nongenetic acclimation to prevailing environmental conditions) for photoperiod (Han et al 1985, Rousi et al 2012, Hayatgheibi et al 2019, Spiecker et al 2019) and for many species rapid evolutionary change should be possible in response to warming (Berteaux 2004, Hamrick 2004). In this context, the genetic composition of natural populations is essential for adaptation (i.e., genetic adaptation to environmental conditions), with high genetic variation facilitating rapid adaptation to new conditions (Hamrick et al 1992, Mueller et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse experiments have indeed shown strong latitudinal clines such that compared with southern populations, northern populations start growth at lower temperature sums in spring (Myking and Heide 1995) and cease growth earlier in autumn (Li et al 2005, Viherä‐Aarnio et al 2005). However, results from field experiments are less clear (Raulo and Koski 1977, Han et al 1985, Hannah 1987, Rousi et al 2012, Viherä‐Aarnio et al 2013, Michelson et al 2018). Han et al (1985), Hannah (1987), Raulo and Koski (1977), and Rousi et al (2012) found no effect on growth and survival after a transfer of up to 24° latitude, whereas Viherä‐Aarnio et al (2013) found a sharp decrease in survival and growth after a transfer of 2° latitude, with the response strongly modified by the common garden site.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of silver birch provenances in field experiments has, however, produced mixed results for fitness and survival and more research is needed for resistance traits. Viherä-Aarnio et al ( 2013) indicated that long transfers (>2 latitudes) lead to a sharp decrease in survival and growth, while successful long-distance transfers of Finnish birches have been reported in North America and South Korea (Han et al, 1985;Rousi et al, 2012).…”
Section: Translocation Experimentsmentioning
confidence: 99%